2021
DOI: 10.1177/08901171211035210
|View full text |Cite
|
Sign up to set email alerts
|

Policy Support for Smoke-Free and E-Cigarette Free Multiunit Housing

Abstract: Purpose: Estimate public support for prohibiting multiunit housing (MUH) e-cigarette and cigarette use. Design: Cross-sectional study. Setting: Data from an online panel survey. Sample: A Fall 2018 nationally representative sample of 3,415 (99.3% response rate) United States (US) adults 18-64 years old. Measures: Policy support for prohibiting MUH smoking and e-cigarette use, sociodemographics, and tobacco perceptions and behaviors. Analysis: Weighted multivariate logistic regression examined predictors of sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…1 ). 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ,…”
Section: Resultsunclassified
See 1 more Smart Citation
“…1 ). 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ,…”
Section: Resultsunclassified
“…Most reports (n = 67) assessed support for hypothetical scenarios, i.e., support for smoke-free places not yet in place without referring to concrete plans for implementation or actual implementation (see Appendix III ). 22 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 33 , 34 , 39 , 42 , 43 , 47 , 48 , 49 , 50 , 51 , 56 , 57 , 58 , 60 , 61 , 63 , 64 , 65 , 66 , 67 , 68 , 71 , 72 , 74 , 75 , 77 , 78 , 79 , 81 , 83 , 85 , 86 , 87 , 89 , 90 , 91 , 92 , 93 , 95 , 99 , 100 , 102 , 103 , 104 , 105 , 106 , 108 , 110 , 112 , 115 , 116 , 119 , 120 , 123 , 124 , 125 , ...…”
Section: Resultsmentioning
confidence: 99%
“…However, a study of college students showed that monitoring the smell and smoke of flammable cigarettes is used as a means of social control, which has an impact on reducing smoking [34]. In most shared residences, non-smoking regulations are imposed around cigarettes [25]. A study showed that a significant proportion of students living in dormitories used e-cigarettes, which influenced the choice of smokers or non-smokers living with them to use e-cigarettes [35].…”
Section: Discussionmentioning
confidence: 99%
“…Cohabitation with family members or relatives also lowers adolescents' risk of smoking because it provides stability in the family structure due to the presence of a primary guardian [21]. In addition, when sharing a living space, such as cohabitation with others or living in a group residential facility, there are formal or informal regulations for the non-smoking zone, which affects the type of tobacco which is used [4,24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation